From Evidence to Policy Supporting Nepal’s Trade Integration Strategy : Diversifying Nepal’s Economy through a Dynamic Services Sector - Hollweg, Claire H. (World Bank, Washington, DC, 2016)
This note looks at the services sector and its dual role for Nepal: as a direct source of exports, and as a provider of key inputs for other sectors of the economy. It identifies sources of potential for services exports, and key obstacles for improved efficiency in the sector. It also provides some policy recommendations to alleviate the observed obstacles, and presents examples of good practices from across the world in terms of services trade performance and reforms. Three of the 12 sectors identified in Nepal’s National Trade Integration Strategy 2015 (NTIS 2015) are services-related. This note assesses Nepal’s trade potential in services, and identifies actionable policy measures that are needed for Nepal to achieve this potential. The framework used to assess Nepal’s trade potential in services starts from the idea that services play a dual role for building export competitiveness in the Nepalese economy. The remainder of this note proceeds as follows. Section I analyzes the direct services export performance of Nepal’s exports relative to comparator countries, when measuring exports in gross or value added terms. It takes a detailed look at performance of Nepal’s priority export potential services sectors. Section II analyzes the indirect services export performance, when services are used as inputs for other sectors’ exports. It takes a perspective of services for cross-cutting export competitiveness. This analysis is undertaken in value-added terms. Section III details the policy implications that arise from this analysis, taking both a cross-cutting and sector-specific point of view.